Solar Energy Harvesting and Management in Wireless Sensor Networks - Muhammad Mazhar Abbas; Mohamed A. Tawhid; Khalid Saleem; Zia Muhammad; Nazar Abbas Saqib; Hafiz Malik; Hasan Mahmood (International Journal of Distributed Sensor Networks)
Wireless networks comprise of small devices that are typically deployed in environments where paucity of energy seriously restricts essential operations. The energy source of these devices decreases very quickly during continuous operation and it is pivotal to replace or recharge frequently the power sources. Sometimes, it is very difficult to perform these functions through conventional methods. One attractive solution to this problem is the use of the energy, scattered around us in the environment. The availability of energy from the environment is random and uncertain. In this paper, we present a model, schematically and analytically, for solar energy harvesting with appropriate energy management. We provide analysis and simulations for a solar cell for standard and different irradiance levels. The power of the storage device is also simulated for different times of the day. The proposed model not only scavenges the energy but also assures the connectivity of the network by optimizing the energy consumption.